Co-movement of Foreign Direct and Portfolio Investments in Central and Eastern Europe - Erzurumlu, Yaman O.; Gozgor, Giray (International Journal of Economics and Financial Issues, 2014)
This paper empirically examines short- and long-run relationships between foreign direct investments (FDI) and volatility of foreign portfolio investments (FPI) in 12 Central and Eastern European (CEE) countries. We use the Generalized Autoregressive Conditional Heteroskedasticity models to calculate volatility of the FPIs. We utilize the second generation panel unit root test, panel-Wald causality test procedure and panel cointegration analysis allowing for structural breaks, and cross-sectional dependence. The results strongly suggest that a decrease in FPI volatility is followed by an increase in FDI in the long-run, and this indicates economies that advance in capital liberalization benefit from increases in FDI. However, the relationship in opposite direction in the long-run is valid in only half of the countries studied. In short-run, we observe that the former relationship is valid only in Turkey, the Czech Republic, and Lithuania; where the latter is valid only in Latvia. Keywords: Central and Eastern European economies; foreign direct investment; foreign portfolio investment; volatility models; panel data estimation techniques JEL Classifications: C50; F21; F32